2003
DOI: 10.1002/jcp.10412
|View full text |Cite
|
Sign up to set email alerts
|

Changes in macrophage function and morphology due to biomedical polyurethane surfaces undergoing biodegradation

Abstract: Monocytes are recruited to the material surface of an implanted biomedical device recognizing it as a foreign body. Differentiation into macrophages subsequently occurs followed by fusion to form foreign body giant cells (FBGCs). Consequently, implants can become degraded, cause chronic inflammation or become isolated by fibrous encapsulation. In this study, a relationship between material surface chemistry and the FBGC response was demonstrated by seeding mature monocyte-derived macrophages (MDMs) on polycarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(103 citation statements)
references
References 43 publications
5
97
1
Order By: Relevance
“…[28][29][30] In a similar manner, MSCs have been shown to modulate immune cell function through a variety of paracrine and juxtacrine effects, though these interactions are not completely understood. Over the past two decades there have been an increasing number of injectable fillers based on chemically modified biomaterials to use for soft tissue wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] In a similar manner, MSCs have been shown to modulate immune cell function through a variety of paracrine and juxtacrine effects, though these interactions are not completely understood. Over the past two decades there have been an increasing number of injectable fillers based on chemically modified biomaterials to use for soft tissue wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…17 Briefly, 0.1% Hoescht Dye no. 33258 was diluted in 10% 10X buffer containing 0.10M Trizma base, 2.0M NaCl, and 0.01M EDTA [in deionized, distilled water (ddH 2 O), pH 7.4] on the day of analysis.…”
Section: Assay Of Dna Content Of Cell Lysatesmentioning
confidence: 99%
“…7,16 The total esterase activity, de novo esterase synthesis, and amount of both CE and MSE in MDMs differed depending on the material surface. 17 The above studies clearly indicated that macrophages respond to small changes in polymer chemistry depending on which PCNU is the seeding surface for the MDMs; however, the mechanism of macrophage activation by these different materials is still unknown. One of the first responses associated with MDMs that occurs with exposure to these materials is the respiratory burst, which is mediated to some extent by protein kinase C (PKC).…”
Section: Introductionmentioning
confidence: 96%
“…Both cell types develop from a common precursor. 29 Since foreign body giant cells (FBGC) are the fusion products of monocytic precursors, which are also the precursors to macrophages, 30,31 the presence of such leukocytes in the wound healing compartment may be of central importance in driving the tissue reaction to the material. These results are similar to a previous investigation.…”
Section: Discussionmentioning
confidence: 99%